2003
DOI: 10.1002/smj.351
|View full text |Cite
|
Sign up to set email alerts
|

Organizational slack and firm performance during economic transitions: two studies from an emerging economy

Abstract: An Erratum has been published for this article in Strategic Management Journal 25(3) 2004, 307. How does organizational slack affect firm performance? Organization theory posits that slack, despite its costs, has a positive impact on firm performance. In contrast, agency theory suggests that slack breeds inefficiency and inhibits performance. The empirical evidence, largely from developed economies, has been inconclusive. Moreover, little effort has been made to empirically test whether such an impact (positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
749
6
17

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 842 publications
(798 citation statements)
references
References 51 publications
26
749
6
17
Order By: Relevance
“…However, other research suggests that when the focus of the items is on more objective characteristics, reliability of single-item scores is often acceptable (Wanous, Reichers, & Hudy, 1997). Further, when managers are within the same firm, prior research suggests it is possible for them to agree and produce ratings with acceptable levels of reliability (Takeuchi et al, 2009). In this study, managers only reported the selection ratio and proportion of employees internally trained.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 95%
See 1 more Smart Citation
“…However, other research suggests that when the focus of the items is on more objective characteristics, reliability of single-item scores is often acceptable (Wanous, Reichers, & Hudy, 1997). Further, when managers are within the same firm, prior research suggests it is possible for them to agree and produce ratings with acceptable levels of reliability (Takeuchi et al, 2009). In this study, managers only reported the selection ratio and proportion of employees internally trained.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 95%
“…The referent for these items was the firm. Although the staffing or training items were completed by a single rater, there is evidence that managers from within the same firm can reasonably agree and produce ratings of reasonable reliability (Takeuchi, Chen, & Lepak, 2009). The survey for managers asked them to respond to the items in reference to 2004, and thus the survey items were designed to capture (retrospectively) all of 2004.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…Slack resources are needed since they can help firms buffer from internal uncertainty and environmental turbulences contestability (Bourgeois 1981;Tan, Peng 2003, Thompson 1967Jansen et al, 2012). Depending on the degree of flexibility, slack resources can be categorized as unabsorbed slack and absorbed slack.…”
Section: Organizational Slack and Its Moderating Effect On Ambidextermentioning
confidence: 99%
“…Organizational slack is measured following prior studies by Nohria and Gulati (1996) and Tan and Peng (2003). The Cronbach"s alpha for the organizational slack measure is 0.696.…”
Section: Exploration and Exploitationmentioning
confidence: 99%
“…Examples include excessive production capacity (Greve, 2003). The latter are resources which are currently not committed to any business activities and thus can be redeployed readily within organizations (Sharfman et al, 1988;Tan & Peng, 2003 Vol. 7, No.…”
Section: The Distinctions Between Human Resource and Financial Slackmentioning
confidence: 99%